FLUID FLOW CHARACTERISTICS IN A SHELL AND TUBE HEAT EXCHANGER WITH SWIRL BAFFLES - Rahman, Aulia; Winarto, Winarto; Siswanto , Eko; Yulianti , Lilis; Kusumastuti , Rizky (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2025)
This paper presents a numerical investigation into the fluid flow and heat transfer characteristics of a shell and tube heat exchanger (STHeX) equipped with baffles that induces swirl flow. A Computational Fluid Dynamics (CFD) model was created to simulate the STHeX behavior, and its accuracy was confirmed by comparing it to the Bell-Delaware method results. The two sets of calculations exhibited good agreement, validating the CFD model. The velocity component of the fluid flow was analyzed both qualitatively and quantitatively. The flow patterns of eddies on the STHeX were carefully examined and their correlation with thermal performance was investigated. This study demonstrates that the swirl flow baffle geometry leads to a more turbulent flow pattern, resulting in an increase in the overall heat transfer coefficient. The findings indicate that the swirl flow baffle enhances heat transfer performance and reduces pressure drop in comparison to a conventional STHeX.